2006
DOI: 10.1007/s10875-006-8904-y
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Pathogenic Anti-dsDNA Antibodies Is Controlled on the Level of B Cells in a Non-Lupus Prone Mouse Strain

Abstract: The SmD1(83-119) peptide is a main target of autoantibodies and T cells in human and murine lupus, but its role in autoimmunity induction remains elusive. Therefore, female Balb/c mice and (NZW x Balb/c)F1 [CWF1] mice with identical MHC haplotype as lupus prone NZB/W mice were immunized with SmD1(83-119). Immunizations of CWF1 mice with SmD1(83-119), but not with the controls (irrelevant peptide, HEL peptide, or saline), induced anti-SmD1(83-119) and anti-dsDNA antibodies and proteinuria not present in Balb/c … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…These data suggest that the T and B cell responses to SmD are strain dependent and some autoantibodies might not be induced in normal mice (20). The lack of epitope spreading in BALB/c mice immunized with SmD in our model system is supported by recent findings of Langnickel et al (21). BALB/c mice immunized with peptide SmD1 83-119 did not generate anti-SmD or anti-dsDNA autoantibodies.…”
Section: Discussionsupporting
confidence: 81%
“…These data suggest that the T and B cell responses to SmD are strain dependent and some autoantibodies might not be induced in normal mice (20). The lack of epitope spreading in BALB/c mice immunized with SmD in our model system is supported by recent findings of Langnickel et al (21). BALB/c mice immunized with peptide SmD1 83-119 did not generate anti-SmD or anti-dsDNA autoantibodies.…”
Section: Discussionsupporting
confidence: 81%
“…In this same study, B cells from tolerized mice induced T cell anergy in vitro (64). Others showed that B cells controlled T cell help and autoimmunity in lupus-prone NZB/W mice (65). We showed previously that Bright is expressed in activated mature B cells in response to a number of stimuli (31).…”
Section: Discussionmentioning
confidence: 69%
“…From the results of the present investigation, RNAPI(S1)-NT (Figure 3a), RNA-PI(S1)-BD ( Figure 3b) and La (Figure 5a) can now be added to the list of proteins and peptides that are capable of inducing an anti-DNA response in nonautoimmune animals. This list includes RNAPI holoenzyme [34], histones [31], the SmD1 83 -119 peptide [32], a SmB/B 0 peptide [33], nRNP A peptides [54] and DNA mimotope peptides [29,30]. Anti-DNA antibodies can, in turn, lead to production of antibodies against a variety of other SLE autoantigens, including anti-RNAPI [35,36] directed against (S1)-NT and -BD (Figure 2a and b), anti-La (Figure 2c), anti-ribosomal P protein (Figure 2d) and anti-Sm/RNP (Figure 2e).…”
Section: Discussionmentioning
confidence: 99%
“…Immunization of normal mice (Balb/c) with nucleosomes or histones leads to the production of anti-dsDNA, anti-Ro, anti-La and antiSm [31]. Immunization with the SmD1 83 -119 peptide leads to anti-dsDNA in the nonlupus prone mouse strain CWF1 but not in Balb/c mice [32]. Immunization of rabbits with a peptide from the Sm B/B 0 antigen results in anti-dsDNA, anti-RNP and anti-Ro (but not anti-La) in a significant fraction of these noninbred, pedigreed animals [33].…”
Section: Introductionmentioning
confidence: 99%